Teachers' efforts to improve students' social skills in social studies learning - Efendi, Bintang Muhammad Sahara; Wiradimadja, Agung (Jurnal Teori dan Praksis Pembelajaran IPS, 2024)
The current condition of students' social skills can be said to be quite apprehensive. Many behaviors reflect low social skills. This research article discusses students' social skills problems at the 7-9 grade junior high school level. Their social skills raise various problems during the learning process in class. Therefore, this article focuses on research with the objectives of 1) describing the condition of the social skills possessed by students in social studies learning and 2) describing the efforts made by social studies teachers to improve students' social skills. This is descriptive qualitative research with data collection techniques: observation, interviews, and documentation. Researchers used purposive and snowball techniques in selecting research subjects. Data analysis techniques use interactive models consisting of 1) data collection, 2) data condensation, 3) display data, and 4) conclusion drawing and verification. Researchers also used data triangulation techniques to check the validity of the data. The results showed that some students had low social skills. To overcome these problems, teachers make various efforts to improve social skills, which are divided into four indicators: 1) skills to comply with rules, 2) valuing skills, 2) communication skills, and 4) teamwork skills.